2013
DOI: 10.1002/pip.2372
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanical strength of monocrystalline, multicrystalline and quasi‐monocrystalline silicon wafers: a four‐line bending test study

Abstract: Quasi-monocrystalline silicon wafers have appeared as a critical innovation in the PV industry, joining the most favorable characteristics of the conventional substrates: the higher solar cell efficiencies of monocrystalline Czochralski-Si (Cz-Si) wafers and the lower cost and the full square-shape of the multicrystalline ones. However, the quasi-monocrystalline ingot growth can lead to a different defect structure than the typical Cz-Si process. Thus, the properties of the brand new quasimonocrystalline wafer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…Previous research on wafer thinning has focused on two aspects: (i) improving existing equipment and techniques for processing, 12,13,18,19 and (ii) studying the mechanics of crack propagation to avoid fracturing. 18−21 While these efforts have led to improvements, the typical method for processing silicon wafers has remained relatively constant for the past six decades.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous research on wafer thinning has focused on two aspects: (i) improving existing equipment and techniques for processing, 12,13,18,19 and (ii) studying the mechanics of crack propagation to avoid fracturing. 18−21 While these efforts have led to improvements, the typical method for processing silicon wafers has remained relatively constant for the past six decades.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was reported that quasi‐mono silicon has higher averaged residual stress than multi‐crystalline silicon, and the strength of the former is weaker than the latter especially when appearance of locally high density defects . To our surprise, the statistical fracture strengths of multi‐crystalline silicon wafers are comparable with or even higher than those of CZ silicon wafers by Weibull distribution. The influence of GBs on the mechanical properties and the weak point in multi‐crystalline silicon wafer are not well understood yet.…”
Section: Introductionmentioning
confidence: 57%
“…The stress fields around GBs are critical in terms of the mechanical stability of the wafer, as they can act as sources for crack formation if additional force is applied . It was reported that quasi‐mono silicon has higher averaged residual stress than multi‐crystalline silicon, and the strength of the former is weaker than the latter especially when appearance of locally high density defects . To our surprise, the statistical fracture strengths of multi‐crystalline silicon wafers are comparable with or even higher than those of CZ silicon wafers by Weibull distribution.…”
Section: Introductionmentioning
confidence: 68%
“…Therefore, an increase in the macroscopic breakage yield during the industrial handling can be expected. It has been verified that there were direct effects of such a high density of defects (Figure 9(a)) in the fracture tension limits of the wafers, as determined by a systematic four-line bending test (FLBT) analysis [10]. By FLBT fitted to the corresponding Weibull distribution analysis, a batch of 50 highly dislocated mono-like wafers exhibited up to ca.…”
Section: Towards the Seed Recyclingmentioning
confidence: 86%